Excess Mortality in Adults from Sao Paulo During the Covid-19 Pandemic in 2020 Analyses of All-Cause and Noncommunicable Diseases Mortality - De Moraes-Ferrari, G (Nature Research, 2023)
In this study, we estimated the excess mortality from all-causes of death and noncommunicable diseases (NCDs) in adults living in the state of São Paulo during the COVID-19 pandemic in 2020. Number of deaths were retrieved from the Mortality Information System before (2017–2019) and during (2020) the COVID-19 pandemic, considering the following underlying causes of death: Neoplasms; Diabetes Mellitus; Circulatory System Diseases, and Respiratory System Diseases. Standardized Mortality Ratio (SMR) were calculated by dividing the mortality rates in 2020 by average mortality rates in 2017–2019, according to sex, age group, geographic location (state, capital, and Regional Health Departments). In 2020, occurred 341,704 deaths in the state of São Paulo vs 290,679 deaths in 2017–2019, representing an 18% increase in all-cause mortality (SMR 1.18) or 51,025 excess deaths during the first year of COVID-19 pandemic. The excess mortality was higher in men (186,741 deaths in 2020 vs 156,371 deaths in 2017–2019; SMR 1.18; 30,370 excess deaths) compared to women (154,963 deaths in 2020 vs 134,308 deaths in 2017–2019; SMR 1.15; 20,655 excess deaths). Regarding NCDs mortality, we observed a reduction in cancer mortality (SMR 0.98; −1,354 deaths), diseases of the circulatory system (SMR 0.95; −4,277 deaths), and respiratory system (SMR 0.88; −1,945). We found a 26% increase in Diabetes Mellitus mortality (SMR 1.26; 2885 deaths) during the pandemic year. Our findings corroborate the need to create and strengthen policies aimed at the prevention and control of NCDs, in order to mitigate the impact of future infectious disease pandemics. © 2023, The Author(s).